2009
DOI: 10.1007/bf03345784
|View full text |Cite
|
Sign up to set email alerts
|

Lack of consistent association of thyrotropin receptor mutations in vitro activity with the clinical course of patients with sporadic non-autoimmune hyperthyroidism

Abstract: Considering the different diagnostic circumstances, therapeutic strategies and the limitations of a systematic analysis of case reports due to the restricted number of case reports and limited follow-up we found no consistent relation of the TSHR mutation's IVA determined by LRA with the CC of patients with SNAH. This may also be due to the action of genetic, epigenetic, and environmental modifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Therefore, our in vitro data show that the genotype alone could not explain the phenotypic severity of our familial cases with the M453T mutation. As suggested previously, other genetic and/or environmental factors are likely to influence the phenotype of nonautoimmune hyperthyroidism (10,11,18,19).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, our in vitro data show that the genotype alone could not explain the phenotypic severity of our familial cases with the M453T mutation. As suggested previously, other genetic and/or environmental factors are likely to influence the phenotype of nonautoimmune hyperthyroidism (10,11,18,19).…”
Section: Discussionmentioning
confidence: 74%
“…To date, ~30 constitutively activating TSHR mutations have been reported in nonautoimmune hyperthyroidism (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(15)(16)(17)(18)(19). Most of the activating mutations are present in TMD 1, 2, 3, and 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27) analyzed a possible genotype-phenotype correlation in a systematic review of the SNAH cases reported to date. They could not find any consistent association between the degree of in vitro activity of each TSHR mutant and the clinical course of patients with SNAH, and concluded that this may be due, at least in part, to the restricted number of case reports and limited follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of genotype-phenotype correlations in nonautoimmune hyperthyroidism have shown no consistent relationship between in vitro activity of the mutant TSHR and the clinical course of the disease (31), suggesting that other genetic, epigenetic, and environmental modifiers, including iodine intake, might also affect clinical features. Although the prevalence of autonomous thyroid nodules causing hyperthyroidism is very low in Japan, where iodine intake is sufficient, the frequency of constitutively active somatic TSHR mutations in patients with this condition is similar to that in iodine-insufficient areas (32,33).…”
Section: Discussionmentioning
confidence: 99%